과학교과의 사회정서학습(Social and Emotional Learning) 적용 가능성 탐색: 과학 교과서의 과학과 사회정서학습 요소 분석 - 박현주; Hyunju Park (과학교육연구지, 2017)
본 논문은 과학과에서 사회정서학습(Science Social and Emotional Learning, SSEL)의 적용 가능성을 탐색하기 위하여 과학과 사회정학습 요소를 제안하고, 그에 따라 중학교 과학 교과서의 물질 분야 및 고등학교 화학Ⅰ 교과서의 내용을 분석하였다. 과학과 사회정서학습의 가능성과 필요성은 과학교육의 목표인 과학적 소양과 과학의 본성에서 찾을 수 있었다. 과학과 사회정서학습의 요소는 '수리(Numeracy),‘ ’정보통신활용(Information and Communication Technology, ICT),‘ ’비판적 사고(Critical Thinking),‘ ’창의적 사고(Creative Thinking),‘ ’사회적 기술(Personal and Social Capability),‘ ’윤리적 이해(Ethical Understanding),‘ ’문화적 이해(Intercultural Understanding)’등으로 구분하여 제시하였고, 그에 따라 과학 교과서 중 물질의 분야 및 화학I 교과서의 내용을 분석하였다. 분석 결과에 따르면, 과학과 물질 분야의 교과서 내용 및 화학Ⅰ 교과서의 내용에 수리, 정보통신활용, 비판적 사고, 창의적 사고가 60~70% 이상 포함되어 있으나, 사회적 기술능력, 윤리적 이해 능력, 문화적 이해 능력 등은 제한적으로 반영된 것으로 나타났다. 교과서의 부족한 요소들에 대해서는 추후 교과서의 내용의 수정 또는 교사의 수업을 통한 보완 등이 필요하다. 또한 과학 교과에서 얻고자 하는 과학적 탐구 능력과 사회정서적 역량을 동시에 기를 수 있는 과학과 활동이나 실험 활동 등 구체적인 적용 방안에 대한 연구가 필요하다. The purpose of this study was to investigate the possibility of Science Social and Emotional Learning(SSEL). The factors of SSEL were suggested, and by utilizing them, the contents of middle school’s science and Chemistry 1 textbook were analyzed. The factors are as follow: numeracy, information and communication technology, critical thinking, creative thinking, personal and social capability, ethical understanding, and intercultural understanding. The results showed that the 60~70% of textbooks put emphasis on numeracy, information and communication technology, critical thinking, creative thinking while some factors were limited in th contents, which were personal and social capability, ethical understanding, and intercultural understanding. Therefore, teacher should try to reconstruct the teaching and learning materials and fill in the deficiencies of SSEL factors through class activities. In addition, it is suggested to study specific application methods such as science activities or experiment activities in detail to meet social and emotional learning.